Game theory and economic analysis : a quiet revolution in economics - Schmidt, Christian, 1938- (Routledge advances in game theory, 2003)
This book presents the huge variety of current contributions of game theory to economics. The reader is taken through a concise history of game theory and exposed to original pieces of work that are significant to game theory as a whole.